The Effects of the Affordable Care Act Medicaid Expansion on Subjective Well-being - Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2019)
This study analyzes the effects of the 2014 Affordable Care Act (ACA) Medicaid expansion on the subjective well-being of individuals in the United States. Using data from the Panel Study of Income Dynamics, we find that the expansion has significantly improved the overall life satisfaction of low-income non-elderly adults. Various sensitivity checks and falsification tests confirm the internal validity. Our findings imply that, without considering psychological benefits, the actual benefits of the ACA Medicaid expansion may be underemphasized.
Keywords: I13; I18; I31; 330; Affordable Care Act Medicaid Expansion; health insurance; subjective well-being; life satisfaction; happiness